Antirheumatoid Artritis Effect of Purslane Herb Extract (portulaca oleracea l.) to Rat (rattus norvegicus) Induced by Complete Freuds Adjuvant - Rizqi Nur Azizah (Journal of Global Pharma Technology, 2016)
Rheumatoid arthritis is an autoimmune disease characterized by chronic inflammation of the joints of hands and feet. The research on antirheumatoid arthritis of ethanol extracts from Purslane (Portulaca oleracea L.) and effective doses of antirheumatoid arthritis. The research used 15 rats divided into 5 groups. Group 1 (1% Na-CMC); group 2 (prednisone) with the dose of 0.511 mg / kgBW; group III, IV and V were given ethanol extract of purslane doses of 100 mg / KgBW, 200 mg / KgBW and 400 mg / kgWW. The animal model of rheumatoid arthritis was made with intraplant injection of 0.1 mL Complete Freund's Adjuvant. The parameters observed were leg volume measurements and arthritis index. The leg volumes of data were analyzed by One Way Anova test followed by the L test while the arthritis index used the Kruskal-Wallis test followed by the Mann-Whitney test. In leg volume measurements, ethanol extract from the red root dose of 400 mg / kg reduced leg volume by 52.49% (p <0.05). Whereas in the arthritis index parameter, the ethanol extract from purslane dose of 400 mg / kg is significantly reduced the arthritis index (p <0.05) with arthritis index reduction by 50%. In conclusion, the ethanol extract from the purslane (Portulaca oleracea L.) with a dose of 400 mg/kg has better activity in treating rheumatoid arthritis in rats.Keywords: Antirheumatoid arthritis, Portulaca oleracea L., complete freund’s adjuvant.